2023
DOI: 10.3389/fcvm.2023.1203093
|View full text |Cite
|
Sign up to set email alerts
|

The inter-chamber differences in the contractile function between left and right atrial cardiomyocytes in atrial fibrillation in rats

Abstract: IntroductionThe left and right atria (LA, RA) work under different mechanical and metabolic environments that may cause an intrinsic inter-chamber diversity in structure and functional properties between atrial cardiomyocytes (CM) in norm and provoke their different responsiveness to pathological conditions. In this study, we assessed a LA vs. RA difference in CM contractility in paroxysmal atrial fibrillation (AF) and underlying mechanisms.MethodsWe investigated the contractile function of single isolated CM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Findings could be explained by the fact that the LA and RA are under different pressures, metabolic and flow conditions, and neural and mechanical regulations [20][21][22]. In recent studies examining certain pathologies, inter-chamber differences and asymmetrical remodeling of the LA and RA could be demonstrated [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings could be explained by the fact that the LA and RA are under different pressures, metabolic and flow conditions, and neural and mechanical regulations [20][21][22]. In recent studies examining certain pathologies, inter-chamber differences and asymmetrical remodeling of the LA and RA could be demonstrated [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Findings could be explained by the fact that the LA and RA are under different pressures, metabolic and flow conditions, and neural and mechanical regulations [20][21][22]. In recent studies examining certain pathologies, inter-chamber differences and asymmetrical remodeling of the LA and RA could be demonstrated [20][21][22]. Several studies have shown that both atria are dilated, and their function deteriorates with arrhythmological consequences in the presence of certain cardiac diseases, even in children [23][24][25].…”
Section: Discussionmentioning
confidence: 99%